ENTERPRISE, ENTREPRENEURSHIP, AND INNOVATION: WHAT THIS MEANS FOR THE NEW HRM PROFESSIONAL AND THE NEW WORKPLACE - Best, Simon; Eftimov, Lјupcho (Dynamic Relationships Management Journal, 2019)
With the fourth industrial revolution underway, this paper suggests that one way of responding to the changing way we work is for HRM professionals to develop a deeper and broader understanding of enterprising, entrepreneurial, and innovative behaviors. The paper provides an overview of the changes that are beginning to occur as a result of this revolution and describes what these changes mean to employment. The paper examines the emerging skills needed for the future and argues that many if not all of these skills can be met by matching them to the competencies that make enterprising, entrepreneurial and innovative people successful. The paper looks at the implications for HRM professionals and concludes that a deeper and broader understanding of enterprising, entrepreneurial, and innovative behaviors will be critical for HRM professionals as the nature of work changes.
Keywords: enterprise, entrepreneurship, industrial revolution, innovation, work change